1998
DOI: 10.1126/science.279.5359.2126
|View full text |Cite
|
Sign up to set email alerts
|

Species Distributions, Land Values, and Efficient Conservation

Abstract: Efforts at species conservation in the United States have tended to be opportunistic and uncoordinated. Recently, however, ecologists and economists have begun to develop more systematic approaches. Here, the problem of efficiently allocating scarce conservation resources in the selection of sites for biological reserves is addressed. With the use of county-level data on land prices and the incidence of endangered species, it is shown that accounting for heterogeneity in land prices results in a substantial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
417
2
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 698 publications
(438 citation statements)
references
References 8 publications
9
417
2
4
Order By: Relevance
“…Taken together, these results suggest a richer understanding of conservation effort stands to be gained by analyzing investment strategies along both dimensions (area and dollars invested). Past habitat conservation strategies have been suggested to be largely opportunistic (Ando et al 1998;Scott et al 2001). However, our analyses suggest a generally strategic signal in TNC's investment portfolio.…”
Section: Discussioncontrasting
confidence: 40%
“…Taken together, these results suggest a richer understanding of conservation effort stands to be gained by analyzing investment strategies along both dimensions (area and dollars invested). Past habitat conservation strategies have been suggested to be largely opportunistic (Ando et al 1998;Scott et al 2001). However, our analyses suggest a generally strategic signal in TNC's investment portfolio.…”
Section: Discussioncontrasting
confidence: 40%
“…We feel that the analysis of budget constraints in dollar terms, rather than in terms of number of sites, is an important next step in the analysis. Ando et al (1998) and Polasky et al (2001) have shown that budget constrained solutions that incorporate difference in land costs across sites often lead to distinctly different priorities than do site constraint solutions that ignore such differences.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of these methods to find optimal solutions to the reserve site selection problem include Cocks and Baird (1989), Saetersdal et al (1993), Church et al (1996), Kiester et al (1996), Csuti et al (1997), Pressey et al (1997), Ando et al (1998), Snyder et al (1999), and Polasky et al (2001).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is implicitly assumed that the conservation planner has full information on the (opportunity) costs of procuring land from different landowners, and that all landowners will participate (cf. Ando et al 1998, Williams 1998, Williams and Snyder 2005, Conrad et al 2012. Bamière et al (2013) do assume asymmetric information with respect to the landowners' opportunity costs, but they do not allow for voluntary participation in their auction model.…”
Section: Introductionmentioning
confidence: 99%